A comparison of global indices between the Medmont Automated Perimeter and the Humphrey Field Analyzer. Issue 10 (27th March 2007) - Landers, John; Sharma, Alok; Goldberg, Ivan; Graham, Stuart
Abstract : Background: Two commonly used perimeters in Australia are the Humphrey Field Analyzer II (HFA) and the Medmont Automated Perimeter (MAP). Each device describes the visual field in terms of numerical values called global indices; however, these values are not interchangeable between devices. This study was designed to directly compare the global indices of HFA and MAP visual fields. Methods: 63 subjects who had suspected glaucoma, ocular hypertension or glaucoma, or were normal controls were recruited selectively. Each patient was tested with the MAP and HFA. Global indices were then compared between tests. These included mean deviation (MD) and pattern standard deviation (PSD) from the HFA and average defect (AD) and pattern defect (PD) from the MAP. Results: The MD and PSD results were strongly correlated with the AD and PD results, respectively. The relationship between them could be described in terms of two polynomial equations: AD = 0.94+1.31(MD)+0.02(MD) 2 and PD = 2.21(PSD)–0.05(PSD) 2 –0.006. These non-linear relationships may be the result of differences in testing method (test stimulus spectrum, number of testing locations or background luminance) or differences in the way each global index was calculated. Conclusion: The AD and PD results obtained from the MAP may be substituted for the MD and PSD results from the HFA after appropriate conversion.